On constraint qualifications in mathematical programming - L. I. Minchenko; S. I. Sirotko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article is devoted to the condition of R-regularity (Error Bound Property) in problems of mathematical programming. This condition plays an important role in analyzing the convergence of numerical optimization algorithms and it is a fairly general condition of regularity (constraint qualification) in problems of mathematical programming. The article obtains new sufficient conditions for the presence of R-regularity in problems of mathematical programming.